Analisis Faktor-Faktor yang Mempengaruhi Kualitas Laporan Keuangan Pemerintah Daerah Kota Medan: Studi Kasus pada BKAD Provinsi Sumatera Utara - Nasirwan; Lubis, Anggi Zahwa Yunita; Bhayangkara, Andika; Sitanggang, Endang Maya Sari (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to determine the influence of human resource competence, implementation of government accounting standards, government internal control systems, and use of information technology on the quality of local government financial reports. The research was conducted at the Regional Finance and Asset Agency (BKAD) of North Sumatra Province using a quantitative descriptive approach method. The population in this study were all employees at BKAD North Sumatra Province with a sample of 50 people. Data collection was carried out by distributing questionnaires to respondents. Data analysis used multiple linear regression with the help of SPSS software. The research results show that simultaneously, human resource competence, implementation of government accounting standards, government internal control systems, and use of information technology have a significant effect on the quality of local government financial reports. However, partially, only the government's internal control system and the use of information technology have a significant effect, while human resource competence and the application of government accounting standards do not have a significant effect. These findings underscore the importance of strengthening the internal control system to reduce the risk of material errors in financial reports, as well as the effective use of information technology to increase the accuracy and timeliness of reporting. Although human resource competency and the implementation of government accounting standards did not have a significant influence in this research, these results may be influenced by contextual factors such as the level of training and employee understanding of Government Accounting Standards in BKAD North Sumatra Province. The implication of this research is the need for continuous efforts to improve the quality of regional government financial reports through strengthening internal control systems, optimal use of information technology, and increasing human resource competency through training and socialization of effective government accounting standards. Further research can be conducted by expanding the sample scope and considering other factors that might influence the quality of local government financial reports.